Avaliação de impactos de secas no estado de Sergipe - Batista, Daniela Ferreira (2021)
Risk management seeks to reduce future impacts of droughts through monitoring, preparation of drought preparedness plans and vulnerability reduction. In Brazil, the Brazil Drought Monitor (MSB) represents the first step towards achieving this management model. The MSB is a collaborative process of regular and periodic monitoring of the situation of droughts, through the elaboration of a monthly map. This map results from the combination of indicators and support products and aims to achieve a common understanding about drought conditions, their severity, spatial evolution and time, and their impacts on the agricultural and hydrological sector. An important aspect of this monitoring process is the identification of physical drought, based on natural aspects, disregarding systems subject to human management. The monitor classifies drought into five severity levels ranging from weak to exceptional, and each level is associated with possible impacts that each classification can generate in these two sectors: agricultural and hydrological. The impacts were obtained from the National Drought Mitigation Center, since the MSB is based on the Drought Monitor of the United States, that is, it is not adapted to the reality of Brazil. Identifying local impacts of droughts integrates the process to achieve risk management, in addition, it can contribute to the monitoring of droughts and to the definition of appropriate actions to reduce future impacts of this event. In this context, this research analyzed territories and sectors most impacted by droughts in the state of Sergipe. For this, the relationship between the categories of droughts defined monthly by the MSB, climatological variables and the agricultural and hydrological impacts in these territories of the Sergipe state was determined. At the end of this research it was identified that the Alto Sertão territory was the most impacted regarding the highest average temperatures, higher crop losses of small producers and higher demand in the emergency water supply. In relation to the deviations of precipitation and situation of the reservoirs, the Agreste Central resembled the Alto Sertão. For the Centro-Sul, the main difference was in evapotranspiration deviations, which for this territory remained close to normal. In relation to the sectors surveyed, small producers and the supply of human and animal water were the most impacted by droughts. From the results obtained, changes were proposed in the drought impact table of the Drought Monitor, in order to help decision makers identify appropriate mitigation actions to reduce the impacts of droughts in these territories.